An automatic and patient-specific algorithm to design the optimal insertion direction of pedicle screws for spine surgery templates. - Naddeo, Francesco; Cataldo, Emilio; Naddeo, Alessandro; Cappetti, Nicola; Narciso, Nicola (Medical & Biological Engineering & Computing, 2017)
Many diseases of the spine require surgical treatments that are currently performed based on the experience of the surgeon. For pedicle arthrodesis surgery, two critical factors must be addressed: Screws must be applied correctly and exposure to harmful radiation must be avoided. The incorrect positioning of the screws may cause operating failures that lead to subsequent reoperations, an increase in the overall duration of surgery and, therefore, more harmful, real-time X-ray checks. In this paper, the authors solve these problems by developing a method to realize a customized surgical template that acts as a drilling template. The template has two cylindrical guides that follow a correct trajectory previously calculated by means of an automatic algorithm generated on the basis of a vertebra CAD model for a specific patient. The surgeon sets the template (drilling guides) on the patient's vertebra and safely applies the screws. Three surgical interventions for spinal stabilization have been performed using the template. These have had excellent results with regard to the accuracy of the screw positioning, reduction of the overall duration of the intervention, and reduction of the number of times the patient was exposed to X-rays.